2017
DOI: 10.1111/ajgw.12292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the type of oak barrels employed during ageing on the ellagitannin profile of wines

Abstract: Background and Aims: Ellagitannins released from wood to wine during barrel ageing can affect wine colour and astringency. This work aimed to examine the influence that oak wood type (French or American) and age (first-fill or second-fill) of barrels has on the concentration of individual ellagitannins and their evolution during winemaking and ageing. Methods and Results: The ellagitannin composition of red wines during ageing was determined by HPLC-MS/MS-multiple reaction monitoring. Differences in the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 28 publications
1
24
1
2
Order By: Relevance
“…Regarding the TPI, there was a progressive increase throughout the aging for all wines (Figure 1b). This is due to the transfer of ellagitannins 23 from oak wood, and these tannins are derived from galloyl units esterified to a sugar core. 24 Once the aging period was over, significant differences were found between AF, TB, Sylvain Reśerve (SR), and STP barrels.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the TPI, there was a progressive increase throughout the aging for all wines (Figure 1b). This is due to the transfer of ellagitannins 23 from oak wood, and these tannins are derived from galloyl units esterified to a sugar core. 24 Once the aging period was over, significant differences were found between AF, TB, Sylvain Reśerve (SR), and STP barrels.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors as the oak species ( Quercus robur L., Quercus petraea Liebl . ), the geographical origin [11,12,13], the age [14], the topography [15,16] and the geographic location of the wood piece in the trees [14,17] as well as the processing of wood in cooperage such as the type and duration of seasoning and toasting [18,19,20,21] can influence the content of the ellagitannins in oak wood [9]. Moreover, the age of the barrels is also important, since it has been reported that the levels of extracted ellagitannins are much lower in old barrels [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The glucopyranosic ellagitannins are another subclass of hydrolyzable tannins, such as punicalagin that occurs in pomegranates. All these ellagitannins may be present in (alcoholic) beverages, such as wine and fruit juices produced from red grapes or from pomegranate. , Punicalagin can occur in beverages due to its presence in pomegranates, while castalagin and vescalagin can occur only in wines that are aged in oak barrels or that are macerated with oak slaves or chips due to their extraction from wood by the alcoholic solution or even when some commercial tannins from oak or chestnut are added to these beverages. The presence of these ellagitannins in beverages is important because they can affect the chemical profile, evolution and, at the end, organoleptic properties of the beverage.…”
Section: Introductionmentioning
confidence: 99%